SOCIAL REPRESENTATION OF THE NURSE IN THE ORGAN DONATION PROCESS - Gloy Alves Andrade, Ray; Maria Schefer Cardoso, Sandra (Health and Society, 2023)
Brazil is a world reference in the field of transplants and has the largest public transplant system in the world. It is known to a large part of the population that thousands of people live with the hope of carrying out the transplant, however, the reality shows a discrepancy between the number of people waiting for an organ and the number of potential donors. Objective: to identify the importance of organ donation and the role of nurses (a) in front of a multidisciplinary team in the process of capturing organs and tissues for donation and transplantation. Materials and method: This is a narrative bibliographic review study. And it had as inclusion criteria the search for material published in the period from 2019 to 2022, in Portuguese and English languages in virtual databases such as BVS and Bireme. Eighteen publications were selected for data collection. Results: three subjects were listed in category format, such as Brazilian guidelines for organ donation; Biovigilance in organ donation; Social representation of nurses in organ donation. Conclusion: It is essential to look at the professional with the aim of offering constant and systematic technical and emotional support, which contributes to the care provided to family members.